Job insecurity, fear of litigation, and mental health among expatriate nurses. Issue 3 (2nd April 2020) - Saquib, Juliann; Taleb, Mohammed; AlMeimar, Redaallah; Alhomaidan, Homaidan T.; Al-Mohaimeed, Abdulrahman; AlMazrou, Abdulrahman; AlShaya, Sultan S.; Saquib, Nazmus
Abstract: The objective was to assess whether job insecurity and fear of litigation were correlates of depression, anxiety, and stress among expatriate nurses in Saudi Arabia. The participants included 977 expatriate nurses working in Al-Qassim, Saudi Arabia who completed an online survey that assessed depression, anxiety, and stress (using DASS-21) as well as demography, lifestyle, and job characteristics. Mean age was 32 years and 60% of nurses were from India/Pakistan. Twenty-four percent of nurses reported job insecurity, and 18% reported a fear of litigation. Severe depression, anxiety, and stress were significantly higher among nurses who always felt insecure about their job (compared to never) and among those who always feared litigation (compared to never). We concluded that job insecurity and fear of litigation were significant correlates of severe depression, anxiety, and stress among expatriate nurses.